TEKNIK BUDIDAYA, PRODUKSI, DAN PENERAPAN GOOD MANUFACTURING PRACTICES DI PT MADU PRAMUKA - Ervina Mela; Nabilla Mutia Rizki (Institute of Computer Science (IOCS), 2023)
Honey is a food product with high nutritional and economic value. One way that can be done to maintain the quality of its products is to apply proper beekeeping techniques and Good Manufacturing Practices (GMP). This study aims to determine beekeeping techniques, production, and implementation of GMP at PT Madu Pramuka. The data were obtained through observation, interviews, and literature study, while the results were analyzed descriptively. Research shows that at PT Madu Pramuka beekeeping techniques include making beekeeping support tools, beekeeping, supervision, cleaning, feeding, and the honey harvesting process. Honey production is done through stage 1 screening, checking water content and sensory testing, stage 2 screening, ripening, packaging, and storage. GMP implementation has been carried out on company location, buildings, production equipment, water supply, sanitation facilities, employee health and hygiene, maintenance and sanitation programs, storage, production process control, food labeling, product recall, and employee training.